Morphological Differences in the Human Sacrum: Gender Estimation using 3D Scans Anatomy and Forensic Medicine - Ahmad Raza Khurram, Tehreem Abaid, Zahid Ali Kaimkhani, Talha Naeem Cheema, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Determining sex from skeletal remains is a cornerstone of forensic anthropology and anatomy, with the pelvis and sacrum providing the most reliable indicators due to their structural and functional adaptations. Objective: This study aimed to analyze morphological differences in the human sacrum using 3D scans and to evaluate the accuracy of various sacral morphometric parameters for gender estimation, using discriminant and receiver operating characteristic (ROC) analyses. Methodology: A total of 55 adult human sacra (28 male and 27 female) were examined using high-resolution 3D scanning. Parameters, including sacral width, length, index, anterior curvature index, and S1 body dimensions, were measured digitally. Results: Significant sexual dimorphism was observed across multiple sacral parameters. Females had a wider and shorter sacrum (mean sacral index: 103.8 ± 6.4), while males exhibited longer, narrower, and more anteriorly curved sacra (mean sacral index: 90.7 ± 5.9; p < 0.001). Discriminant analysis achieved 87.3% overall classification accuracy, with cross-validation maintaining 85.5%. Conclusion: It is concluded that the sacrum exhibits marked sexual dimorphism, and 3D morphometric evaluation offers a precise, reproducible, and objective method for gender estimation. Sacral index, anterior curvature, and width are the most reliable indicators, making 3D sacral analysis a valuable tool in forensic identification and anatomical research. Keywords: Sacrum, Sexual dimorphism, Gender estimation, 3D scanning, Forensic anthropology, Morphometry.